Existence and uniqueness of positive solutions for a class of fractional differential equation with integral boundary conditions - Feng, Haixing; Zhai, Chengbo (Nonlinear Analysis: Modelling and Control, 2017)
The purpose of this paper is to investigate the existence and uniqueness of positive solutions for a class of fractional differential equation with integral boundary conditions. Our analysis relies on two fixed point theorems of a sum operator in partial ordering Banach space. The main results obtained can not only guarantee the existence of a unique positive solution, but also be applied to construct an iterative scheme for approximating it.